2009
DOI: 10.2465/jmps.080929
|View full text |Cite
|
Sign up to set email alerts
|

Metastable transformations of eclogite to garnetite in subducting oceanic crust

Abstract: The eclogite -garnetite transformation experiments were conducted at 11 GPa and 1000 -1550 °C using synthesized polycrystalline eclogite with MORB composition as a starting material. We found that the eclogite -garnetite transformation proceeds by two stages, (1) precipitation of majoritic garnet from clinopyroxene and (2) formation of majoritic garnet from original pyropic garnet by absorption of clinopyroxene. The 1st stage in the transformation proceeds at 1000 °C for 180 minutes, however the 2nd stage was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…During the calculation, we used the HT‐BM3‐EoS and the obtained thermoelastic parameters of eclogitic garnets and omphacites. In this model, the eclogite consists of 20 vol% garnet, 75 vol% omphacite, and 5 vol% coesite (Nishi et al, ), and the densities of eclogite assemblages are estimated by using a Voigt‐Reuss‐Hill average (Hill, ). This model assumes that the eclogitic garnets and omphacites metastably survive to 550 km, while the coesite‐stishovite transition occurs at ~9 GPa (Nishi et al, ).…”
Section: Geophysical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the calculation, we used the HT‐BM3‐EoS and the obtained thermoelastic parameters of eclogitic garnets and omphacites. In this model, the eclogite consists of 20 vol% garnet, 75 vol% omphacite, and 5 vol% coesite (Nishi et al, ), and the densities of eclogite assemblages are estimated by using a Voigt‐Reuss‐Hill average (Hill, ). This model assumes that the eclogitic garnets and omphacites metastably survive to 550 km, while the coesite‐stishovite transition occurs at ~9 GPa (Nishi et al, ).…”
Section: Geophysical Implicationsmentioning
confidence: 99%
“…In this model, the eclogite consists of 20 vol% garnet, 75 vol% omphacite, and 5 vol% coesite (Nishi et al, ), and the densities of eclogite assemblages are estimated by using a Voigt‐Reuss‐Hill average (Hill, ). This model assumes that the eclogitic garnets and omphacites metastably survive to 550 km, while the coesite‐stishovite transition occurs at ~9 GPa (Nishi et al, ). The used thermoelastic parameters of eclogitic garnets and omphacites (this study) and coesite and stishovite are shown in Table S10.…”
Section: Geophysical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Geodynamic models estimate the temperature in the stagnant slabs are lower than 900 ∘ C and can be as low as 500 ∘ C in regions such as Tonga (Ganguly et al, 2009;King et al, 2015). It has been reported that, in cold environment (<1,400 ∘ C), the diffusion between pyrope and majorite garnet is slow, making the preservation of the light metastable pyroxene possible, which changes the density of the slab and therefore affects its morphology and buoyancy (Agrusta et al, 2014;Faccenda & Dal Zilio, 2017;King et al, 2015;Nishi et al, 2008Nishi et al, , 2009Nishi et al, , 2011Nishi et al, , 2013Van Mierlo et al, 2013). As a consequence, the metastability of pyroxene and the kinetics of postpyroxene transformations below 1,000 ∘ C have been suggested to play an important role in slab dynamics (Faccenda & Dal Zilio, 2017;Nishi et al, 2011;Van Mierlo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The actual growth rate determined in this study is much faster than that estimated in the previous study (Figure 3). The back transformation rate is not controlled by Si self‐diffusion as simply assumed in the previous study, but is more likely to be controlled by Mg 2+ + Si 4+ ↔ 2Al 3+ or more complex diffusions involving plural ions [ Nishi et al , 2009]. Furthermore, transformation microstructures suggest that the small grains of pyropic garnet and clinopyroxene are elongated along grain boundaries of majoritic garnet (Figure 2), which implies that the chemical diffusion effectively occurs at the grain boundaries rather than the interior of the parental grain.…”
Section: Resultsmentioning
confidence: 99%